SPEAKING PROBLEM OF JUNIOR HIGH SCHOOL STUDENTS - Pardede, Ezrauli; Sitanggang, Monika Meita; Saragih, Sari Sahnita (Transpublika Publisher, 2022)
The research aims to find the difficulties and problem in speaking English which are mostly faced by Junior High School students. This research used qualitative research method. This research instrument is observation, explaining and applying Presentation Production Method (PPP) method. Based on the results, it was found some speaking difficulties, they are : (1) Difficulty in listening and speaking, (2) Lack of vocabulary, (3) Hard to focus, (4) Inhibition (Lack of confident, worried about making mistakes, fearful, or shy of the attention that they speech attract), (5) Nothing to say (Cannot think of anything to say, or they have no idea to express themselves), (6) Low participation. Speaking is a means of communication which affects our daily lives. In relationship, communication allows you to explain to someone what you are going through and what your needs are.